Grief as method: topographies of grief, care, and fieldwork from Northwest Arkansas to New York and the Marshall Islands - Mitchell-Eaton, Emily (Gender, place and culture : a journal of feminist geography, 2019)
When we grieve during fieldwork, our grief forms new geographies of knowledge production and emotion. In this article, I use autoethnography to theorize my grief during fieldwork following the death of my sister. I examine grief's methodological implications using the concept of 'grief as method,' an emotionally-inflected practice that accounts for the vulnerability produced by grief. By centering vulnerability, 'grief as method' also urges researchers to consider the practices and politics of 'caring with' our research subjects and caring for ourselves, raising larger questions about the role of care in research. Furthermore, this article demonstrates how grief's geographical features-its mobility, its emergence in new sites and landscapes, and its manifestation as both proximity and distance-shape 'grief as method' profoundly. I examine grief's spatial implications by building on Katz's 'topography' to theorize a 'topography of grief' that stitches together the emotional geographies of researchers, blurring both spatial divisions ('the field' vs. 'the not-field') and methodological ones (the 'researcher-self' vs. the 'personal-self'). If we see grief as having a topography, then the relationships between places darkened by grief come into focus. Moreover, by approaching grief methodologically, we can better understand how field encounters-relationships between people-are forged through grief. 'Grief as method,' in offering a spatial analysis of grief's impact on fieldwork, envisions a broader definition of what engaged research looks like and where it takes place.